Metabolic profiling of glyphosate-resistant sourgrass (Digitaria insularis) - Gazola, Tiago [UNESP]; Bianchi, Leandro [UNESP]; Dias, Marcio Furriela [UNESP]; Carbonari, Caio A. [UNESP]; Velini, Edivaldo D. [UNESP] (Cambridge Univ Press, 2020)
Putative glyphosate-resistant sourgrass was collected to determine its resistance level and to evaluate its metabolic profile after resistance. Although accumulation of shikimic acid is known to occur in glyphosate-susceptible populations, differences in the ability of resistant (R) and susceptible (S) biotypes to accumulate quinic acid, salicylic acid, and aminomethylphosphonic acid (AMPA) have been studied to a lesser extent. Our objective was to confirm glyphosate resistance in sourgrass and to understand the metabolic profile of these plants in response to the herbicide. Greenhouse experiments were carried out from January 2016 to June 2018. There were no significant differences in glyphosate translocation in the plants. No metabolism of glyphosate to AMPA was observed; therefore, metabolism of glyphosate to AMPA is not a mechanism in R biotypes. S biotypes showed higher concentrations of shikimic acid and quinic acid before glyphosate and accumulated less of both secondary acids in treated leaves 72 h after glyphosate application. Resistant biotypes showed higher concentrations of salicylic acid before glyphosate application.
Keywords: AMPA; EPSPS; herbicide resistance; quinic acid; salicylic acid; shikimic acid